Effect of lateral size of graphene nano-sheets on the mechanical properties and machinability of alumina nano-composites. Issue 6 (1st May 2016) - Porwal, Harshit; Saggar, Richa; Tatarko, Peter; Grasso, Salvatore; Saunders, Theo; Dlouhý, Ivo; Reece, Mike J.
Abstract: Graphene Nano-Sheets (GNS) with different lateral sizes (193, 373 and 1070 nm) were produced using liquid phase exfoliation and controlled centrifugation. Alumina-GNS (0.8 vol%) composites with different size GNS were consolidated using spark plasma sintering. The fracture toughness, hardness and elastic modulus of the composites decreased with increasing GNS size. Microstructural investigation of the composites suggested that their mechanical properties were directly related to: (1) average number of GNS present per unit volume in composite; and (2) relative size of GNS to alumina grains. Small size GNS resulted in a 35% improvement of fracture toughness of alumina-GNS composite. The mechanism of crack propagation changed as the size of the GNS increased. The smaller size GNS produced various toughening mechanisms, while the larger size GNS, with similar size to the alumina grains, resulted in grain boundary sliding. The composite with larger size GNS was machinable using ordinary tungsten carbide drill bits.